Smart Talk About Cervical and Breast Cancer in Women of Reproductive Age - Donny Richard Mataputun; irman Irman; Mia Atlantic (Karya Kesehatan Siwalima, 2025)
Background: Cervical cancer and breast cancer are two leading causes of cancer-related mortality among women in Indonesia. Low levels of knowledge and awareness in the community, particularly among Women of Reproductive Age (WRA), regarding early detection remain a serious challenge in cancer prevention and management. Objective: This activity aims to improve WRA’s knowledge and awareness of the importance of early detection of cervical and breast cancer through a community-based educational approach. Method: This community service program employed a pre-experimental one-group pre-test and post-test design. The intervention was carried out through education using the peer group method, educational video screening, and discussion sessions with cancer survivors. Data were collected using pre-test and post-test questionnaires and analyzed descriptively. Results: Prior to the educational intervention, the majority of respondents (52.3%) had low levels of knowledge. After the intervention, a significant improvement was observed: respondents with good knowledge increased to 47.7%, while those with poor knowledge decreased to 11.4%. Conclusion: Peer group- and video-based educational activities proved effective in enhancing WRA’s knowledge and awareness regarding the importance of early cancer detection. This educational model is recommended for broader implementation as a promotive and preventive strategy in women’s cancer prevention.